Ecology and management of plum curculio, Conotrachelus nenuphar [Coleoptera :Curculionidae], in apple orchards - Racette, G.; Chouinard, G.; Vincent, C.; Hill, S.B. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
Plum curculio (Conotrachelus nenuphar) is a native pest of pome and stone fruit in eastern North America. It is a key pest of apple (Malus pumila) orchards in Quebec. In spring, adults disperse primarily from woodland overwintering sites to apple orchards. Before fruit set, the beetles are mainly nocturnal. As fruits become available for oviposition, adults extend their activity to the daytime. Full grown larvae found in dropped apples in June (June drop) enter the soil to pupate. The summer brood emerges in August, feeds on the remaining fruit throughout the fall and then disperses to suitable overwintering sites. Little is known of its community and host plant relationships, dispersal behavior, factors influencing its mode of locomotion, choice of food sources, overwintering sites, micro-habitat selection, orientation, and action threshold. Commercially available biocontrol agents are not effective, and convenient and reliable monitoring techniques for the timing of sprays have not been developed. However, recent field and insectary studies on the behavior and activity of plum curculio adults may allow us to improve the efficiency of control strategies. These findings are presented here, together with their implications for control of the plum curculio by modifying its habitat, and by better timing and location of sprays and other interventions. This paper also includes brief reviews of biological controls, insect growth regulators, and genetic controls for plum curculio.